2019
DOI: 10.25170/djm.v18i2.2221
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Successful Treatment of Pulmonary Tuberculosis Patients With the Availability of Treatment Supporter in Atma Jaya Hospital

Abstract: Introduction: One of the biggest health problems faced by community is pulmonary tuberculosis (TB).TB is an respiratory tract infectious disease caused by Mycobacterium Tuberculosis. World Health Organization (WHO) recommends TB treatment with Directly Observed Treatment Short-course (DOTS) strategy, one of which is through the help of treatment supporter (PMO or Pengawas Minum Obat) who supervises the patient during the treatment period. Methods: This was an analytic descriptive study with cross section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…Several factors influence the successful treatment of TB patients, including socio-economic status, knowledge, stress levels, and ease of access to health services (6,7) . The successful treatment of TB patients is beneficial in suppressing the spread of TB disease both in Indonesia and around the world.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several factors influence the successful treatment of TB patients, including socio-economic status, knowledge, stress levels, and ease of access to health services (6,7) . The successful treatment of TB patients is beneficial in suppressing the spread of TB disease both in Indonesia and around the world.…”
Section: Introductionmentioning
confidence: 99%
“…PMO itself is the third point in the DOTS strategy of the five WHO components (8,9) . Based on research conducted by Dailami et al showed that PMO was not significantly related to the success of treatment for TB patients (7) . The quality of PMO in supervising TB patients taking medication will also tend to affect the success of treatment.…”
Section: Introductionmentioning
confidence: 99%